Relationship Between Type 1 Diabetes Mellitus and Insulinoma-Associated Antigen-2 Autoantibodies in Karbala Province - Hamadi Abid, Qasim; Abbas Khalaf, Asaad (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Case control study was conducted at Imam Al-Hussein Medical City and Imam Al-Hassan Al-Mujtaba Hospital in Karbala, and it included information about changes in some immunologic parameters in type 1 diabetes mellitus(T1DM) patients. The study comprised 30 healthy and 60 patients aged 5 to 20 years from female and male between January 2024 and October 2025. This study measured immunological alterations include antibodies levels such as Insulinoma Associated Antigen-2 autoantibodies (IA-2A), immunoglobulins (IgM), Proinflammatory cytokines (IFN-γ) and anti-inflammatory cytokines (TGF-β1). The present study discovered that There was a significant increase (P≤0.01) in IFN-γ, TGF-β1, IA-2A and IgM in patients group compared with healthy group. The goal of this research is to investigate the immunological profile of patients with T1DM in Kerbala Province by analysing the levels of IA-2 autoantibodies (IA-2A), interferon-gamma (IFN-γ), transforming growth factor-β1 (TGF-β1), and immunoglobulin M (IgM). The purpose of this study is to ascertain how these immunological markers relate to the pathophysiology of type 1 diabetes, ascertain their possible roles in the disease's progression, and find patterns that could help with early diagnosis, better monitoring, and a deeper comprehension of the autoimmune mechanisms underlying T1DM in the local population.